(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The objective of this article was to highlight names and profiles of actresses from the São Luís amateur theater of the early 20th century. This theme was supported by the absence of records of women’s names in the city’s dramatic societies between 1901 and 1919, observed in the local press. Contrary to the context prior to 1920, from then onwards there is a diffusion, in local newspapers, of the names of amateur actresses. Who and what were the scenic profiles of the actresses who challenged social dogmas and stood out on the stages of the São Luís amateur theater at the beginning of the 20th century? These names lost in the history of São Luís theater were listed based on documentary research centered on newspapers of the time, since there is a hiatus in this theme until then. The introductory character of this record is in line with the macro problem verified in several fields of knowledge, which try to recover a memory or image supplanted in History, by gender interests and moral perspectives.